Voicing The Reality of Colonialized Women in The Novel ‘Belenggu’ By Armijn Pane - Tang, Muhammad Rapi; Ridwan, Ridwan; Junaedi, Inayah Maharezki (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
This study explores the representation of women's subjugation during the colonial period in Indonesia through Armijn Pane's novel